Do skin bacteriostatic agents reduce acute radiodermatitis in breast cancer patients? A prospective interventional study - Xiaomeng Lu; Chao Wei; Chuang Li; Jiahui Liu; Wentong Yang; Fang Zhang; Zhikun Liu; Wenhui Geng; Yanhong Zhou (PLoS ONE, 2025)
Objective Radiodermatitis is the most prevalent complication in breast cancer patients undergoing radiotherapy. Emerging evidence suggests a correlation between radiodermatitis and Staphylococcus aureus colonization. The aim of our study was to explore whether the application of skin bacteriostatic agents (a sterile liquid dressing containing fucoidan oligosaccharides with anti-Staphylococcus aureus activity) could mitigate acute radiodermatitis in breast cancer patients. Methods We conducted a prospective interventional study, enrolling breast cancer patients receiving outpatient radiotherapy at our institution from July 1, 2023, to January 31, 2024. Patients were divided into an experimental group and a control group based on the usage of skin bacteriostatic agents. The first outcome was evaluated using the Radiation Therapy Oncology Group (RTOG) criteria. The second outcome was the patient’s reported symptoms of radiodermatitis, which included itching, pain, tightness, burning and swelling. The third outcome was whether the usage of skin bacteriostatic agents delayed the onset of self-reported radiodermatitis symptoms. Results A total of 183 patients were enrolled, comprising 101 breast-conserving patients (21 in the experimental group, 80 in the control group); and 82 mastectomy patients (26 in the experimental group, 56 in the control group). The experimental group showed a significantly lower grade of radiodermatitis compared to the control group in both breast-conserving and mastectomy patients (P < 0.05). Patient-reported symptoms of radiodermatitis included itching (54.6%), pain (48.1%), tightness (21.9%), burning (11.5%), and swelling (17.5%), but there was no difference between the two groups and onset in radiodermatitis. Further analysis indicated that hypofractionated radiotherapy could reduce the severity of radiodermatitis and itchiness. Conclusion Skin bacteriostatic agents used during radiotherapy can reduce the severity of radiodermatitis in breast cancer patients, although it does not alleviate self-reported symptoms of dermatitis. Hypofractionated radiotherapy is recommended to reduce the severity of radiodermatitis.